Perinatal loss as a crisis event in a woman’s life - Pergamenshchik, Leonid A.; Petrazhitskaya, Elena A. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
The actual problem of perinatal loss as a unique type of psychological trauma in a woman’s life is considered in the article. Psychological and social consequences of perinatal loss, its specific features affecting the process of coping with grief are described in detail. The results of empirical research of the state of psychological well-being and attitude to the concept of subjective dimension of the path of life in temporal aspect of women with experience of perinatal loss are presented. Perinatal loss is a threat to the development of depression and post-traumatic stress disorder. Self-image, basic beliefs about own life change after perinatal loss, as well as the subjective picture of a woman’s life path is changing. The findings are crucial for the development of basic strategies of psychological support of women in the situation of perinatal loss.